Uptake of homologous single-stranded fragments by superhelical DNA: a possible mechanism for initiation of genetic recombination. - Holloman, W K (1975)
Superhelical [3-H]DNA (replicative form I, RFI) of bacteriophage phiX174 slowly but spontaneously took up 32-P-labeled homologous single-stranded fragments at 4 degrees. Uptake was accelerated by heating to 75 degrees. RFI did not take up single-stranded fragments derived from DNA of Escherichia coli or from separated strands of phage lambda. Uptake was inhibited by low concentrations of ethidium bromide. Relaxed circular phiX174 DNA did not take up homologous fragments. Per molecule of RFI, the complexes contained as much as 90 nucleotide residues of homologous fragment. The 32-P-lebeled fragments were largely resistant to digestion by exonuclease I, and were not displaced by heating complexes at 60 degrees for 1 min in 16 mM or 100 mM NaCl. Under comparable conditions of temperature and salt all of the fragments were displaced from complexes in which at least one phosphodiester bond was cleaved by pancreatic DNase, but a significant fraction of the fragments was retained in complexes that were relaxed by digestion with S1 nuclease. These observations are interpreted to mean that S1 nuclease digested the plus (viral) strand of the recipient RF at the site of uptake in some instances. Transfection of E. coli by heterozygous complexes produced recombinant progeny, thereby showing that genetic information can be transferred from the fragment of plus strand to progeny plus strands. We propose that both uptake of a third strand by superhelical DNA and the action of nucleases on the resulting complex may simulate early steps in genetic recombination.